Comment on Rosell-Cardona et al. Dietary Spray-Dried Porcine Plasma Reduces Neuropathological Alzheimer’s Disease Hallmarks in SAMP8 Mice. Nutrients 2021, 13, 2369 - Artemissia-Phoebe Nifli (MDPI AG, 2021)
Interventions focusing on dementia risk and/or dementia modification in association with senescence are essential, given the unfavourable demographics [...]